Anti-algal activity of the 12-5-12 gemini surfactant results from its impact on the photosynthetic apparatus - Konrad Krajewski; Katarzyna Łudzik; Aneta Żabka; Justyna Teresa Polit; Anna Zawisza; Janusz Maszewski (Scientific Reports)
Abstract A rapid amplification of algal population has a negative impact on the environment and the global economy. Thus, control of algal proliferation is an important issue and effective procedures which reduce algal blooms and control algal fouling are highly desired. Gemini surfactants are considered to have a low environmental impact, therefore they seem to be a promising group of detergents which could reduce algal blooms in water systems. Furthermore, due to their emulsifying properties they could replace algaecides added to antifouling paints and decrease algae adhesion to various surfaces. In this study the toxic effect of the 12-5-12 gemini surfactant was investigated on Chlorella cells and close attention was paid to a potential mechanism of its action. At the high cell density (10.05 × 107 cells/mL) a dose-dependent cell death was found and the IC50 value was reached at the concentration of 19.6 µmol/L after 72-h exposure to the surfactant. The decrease in chlorophyll autofluorescence shows that the photosynthetic apparatus seems to be the target of the tested compound. The presented studies indicate that gemini surfactants could effectively reduce algal blooms in water systems, and if added to paints, they could decrease algal growth on external building walls or other water immersed surfaces.